A CROSSECTIONAL STUDY OF NUTRITIONAL CULTURE ON THE ROLE OF A FATHER IN MADURESE FAMILY AS A EFFORT TO PREVENTING TOTAL STUNTING IN BANGKALAN DISTRICT - Fitriah -; Mustofa Haris; mufarika mufarika (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
In preventing stunting, fathers have a big role in the first 1000 days of life, a father plays a role in maintaining the nutritional stability of the family and provide the psychological needs of mothers and children. Culture also determines how the family pattern of the family fulfill the nutrition of children under five years old. The purpose of this study was to determine the role of fathers in the nutritional culture care for the Madurese family as an effort to prevent stunting in toddlers. The research design used was observational with a cross sectional approach. The research variables include exogenous variables of Madura society parenting culture, the role of fathers and endogenous variables of stunting prevention. The research population of toddlers aged 2-4 in the play group in Bangkalan District in 2021 amounted to 31 schools. The number of samples is 270 toddlers. Sampling technique using Cluster Random Sampling. The instrument used for data collection is a questionnaire. Structural equation modeling-SEM data analysis technique based on variance or component based SEM, which is called partial least square (PLS). The results showed that the culture of nutrition care for the Madurese family affects the role of fathers in preventing stunting in toddlers, the culture of nutritional care in the Madurese family affects the prevention of stunting in toddlers and the role of the father affects the prevention of stunting in toddlers by the family. This shows that fathers have a big role in the growth process of toddlers in fulfill the needs of nutritions. The culture that exists in the Madurese family should not be an obstacle for fathers to play a role in the growth and development of toddlers to prevent stunting